"E.E. Forward, Ralph Pike and Ernestine Pike" - Rorke Family (1935)
Ernest Edward Forward with grandson Ralph Forward Pike and daughter Ernestine (Forward) Pike, standing outside of a house. Ernest Edward Forward (1859-1944), son of Capt. Mark William Forward and Mary (Bemister) Forward, was born at Carbonear on 29 May 1859. He married Tryphena Butt on 24 June 1885, and had three daughters: Ernestine, Hilda and Kathleen. Ernest Forward died on 14 April 1944. His daughter Ernestine was born at Carbonear on 24 April 1887. She married Arthur S. Pike at Carbonear on 25 September 1913 and had 3 sons: Ernest, Arthur Jr. and Ralph. She died at Providence, Rhode Island on 22 March 1950. Her son Ralph was born in 1924. He married a woman named Elizabeth and they had two sons, Troy and Mark. He was an orthopedic surgeon in Rhode Island, USA. Dr. Pike died in 1985. The Rorke Family Photograph Collection contains 301 black and white and 28 colour photographs of the Rorke Family of Carbonear, Newfoundland, as well as the Forward and Bemister families from that area who are linked to it by marriage. Although spanning from the 1840s-1970s, most photos are from 1900-45, showing family events, homes and Newfoundland and Labrador locations. There is also an album of photos taken while James Rorke attended the Leys School in Cambridge, England.